Potent and selective pharmacodynamic synergy between the metabotropic glutamate receptor subtype 2–positive allosteric modulator JNJ‐46356479 and levetiracetam in the mouse 6‐Hz (44‐mA) model. (23rd January 2018) - Metcalf, Cameron S.; Klein, Brian D.; Smith, Misty D.; Ceusters, Marc; Lavreysen, Hilde; Pype, Stefan; Van Osselaer, Nancy; Twyman, Roy; White, H. Steve
Summary: Objective: We previously demonstrated that positive allosteric modulators (PAMs) of metabotropic glutamate subtype 2 (mGlu2 ) receptors have potential synergistic interactions with the antiseizure drug levetiracetam (LEV). The present study utilizes isobolographic analysis to evaluate the combined administration of JNJ‐46356479, a selective and potent mGlu2 PAM, with LEV as well as sodium valproate (VPA) and lamotrigine (LTG). Methods: The anticonvulsant efficacy of JNJ‐46356479 was evaluated in the 6‐Hz model of psychomotor seizures in mice. JNJ‐46356479 was administered in combination with LEV using 3 fixed dose‐ratio treatment groups in the mouse 6‐Hz (44‐mA) seizure test. The combination of JNJ‐46356479 with LEV was also evaluated in the mouse corneal kindling model. The potential interactions of JNJ‐46356479 with the antiseizure drugs VPA and LTG were also evaluated using fixed dose‐ratio combinations. Plasma levels were obtained for analysis of potential pharmacokinetic interactions for each combination studied in the mouse 6‐Hz model. Results: JNJ‐46356479 was active in the 6‐Hz model at both 32‐mA and 44‐mA stimulus intensities (median effective dose = 2.8 and 10.2 mg/kg, respectively). Using 1:1, 1:3, and 3:1 fixed dose‐ratio combinations (LEV:JNJ‐46356479), coadministration was significantly more potent than predicted for additive effects, and plasma levels suggest this synergism was not due to pharmacokinetic interactions. Studies in kindled mice further demonstrate the positive pharmacodynamic interaction of LEV with JNJ‐46356479. Using 1:1 dose‐ratio combinations of JNJ‐46356479 with either VPA or LTG, there were no significant differences observed for coadministration. Significance: These studies demonstrate a synergistic interaction of JNJ‐46356479 with LEV, whereas no such effect occurred for JNJ‐46356479 with either VPA or LTG. The synergy seems therefore to be specific to LEV, and the combination LEV/mGlu2 PAM has the potential to result in a rational polypharmacy approach to treat patients with refractory epilepsy, once it has been confirmed in clinical studies.